2016
DOI: 10.11114/bms.v2i3.1809
|View full text |Cite
|
Sign up to set email alerts
|

Do the Characteristics of Independent Directors and Supervisory Board Members Matter in China?

Abstract: This paper investigates and compares the characteristics of independent directors and supervisory board members in Chinese listed firms. The occupational backgrounds of independent directors and supervisory board members in listed firms are very different. Besides, different firms have different preferences in employing independent directors and supervisory board members according to their demands. Moreover, the empirical results show that characteristics of independent directors and supervisory board members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Finally, SSE 180 companies are widely used in studies where listed companies are examined in the Chinese context. For example, Koutmos (2012), Xu and Lin (2016), and Grimminger and Benedetta (2013), all use the SSE 180 in their studies.…”
Section: Samplementioning
confidence: 99%
“…Finally, SSE 180 companies are widely used in studies where listed companies are examined in the Chinese context. For example, Koutmos (2012), Xu and Lin (2016), and Grimminger and Benedetta (2013), all use the SSE 180 in their studies.…”
Section: Samplementioning
confidence: 99%
“…Therefore, it is necessary to understand the situation of the board of directors before looking at the supervisory boards. Accordingly, the second set of questions in the interview focused on the board of directors, with especial focus on the function of independent directors, inspired by the likes of Xu & Lin [13] and Jiaguo [21].…”
Section: Methodsmentioning
confidence: 99%
“…Tian [2] argued that supervisors are mainly focused on questions of legality, whereas independent directors mainly work to assess the efficiency and capacity of the company's operators from an objective angle. However, Xu and Lin [13] suggested that the responsibilities of independent directors and supervisors largely overlap but that neither has real authority to affect management decisionmaking processes.…”
Section: Monitoring Bodies In Chinese Listed Companiesmentioning
confidence: 99%
See 2 more Smart Citations